El transporte urbano y su incidencia socio-económica en tiempos de pandemia por la covid-19 en la ciudad de valencia-ecuador. Estudio de factibilidad para una empresa de comercialización de bicicletas - Cepeda Moreno, Kleber (2021)
This research is entitled “Urban transport and its socio-economic incidence in times of pandemic by covid-19 in the city of Valencia-Ecuador. Feasibility study for a bicycle marketing company ”. Sars Cov 2 is a virus that worldwide has generated problems ranging from health to economic-social. Among the socio-economic factors is that of urban transportation, for this reason, the objective is to precisely analyze the social and economic effects of the decrease in urban transport in the city of Valencia due to covid 19, in addition, a solution is proposed to face the restriction of urban transportation through the commercialization of bicycles, through the proposal of a feasibility study. The deductive, analytical and inductive methods were used, it is descriptive based on defined technical foundations. A field investigation was also carried out with surveys of citizens and transporters of the Cantón Valencia-Los Ríos-Ecuador. The results showed that users understand that the frequent use of urban transport can spread the disease of covid 19, that people are willing to use an alternative means of transport, including bicycles, and that the relationships Social organizations have been affected by the confinement and distancing imposed by the National COE Emergency Operations Committee. Keywords: Urban, socioeconomic and covid-19 transport